2020
DOI: 10.1038/s41374-020-0427-2
|View full text |Cite
|
Sign up to set email alerts
|

Histone H2B induces retinal ganglion cell death through toll-like receptor 4 in the vitreous of acute primary angle closure patients

Abstract: Acute primary angle closure (APAC) is a disease of ophthalmic urgency; lack of treatment can lead to blindness. Even after adequate treatment for APAC, subsequent elevated acute intraocular pressure induces severe neuronal damage which can result in secondary glaucomatous optic neuropathy (GON). Damage-associated molecular patterns (DAMPs) are released from damaged and dead neuronal cells, which induce secondary inflammatory changes and further tissue damage. Our hypothesis is that histone H2B (H2B), which is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Gilthorpe et al [ 44 ] observe upregulated chemotaxis and expression of the activation marker major histocompatibility (MHC) class II by primary murine microglia in the presence of extracellular H1. Munemasa [ 43 ] demonstrates in a murine model of primary acute-closure glaucoma that extracellular H2B induces retinal ganglion degeneration, which is presumably mediated by activation of microglia. To date, the only study to document the pro-inflammatory activity of extracellular histones on human microglia-like cells is by Westman et al [ 39 ], who utilize THP-1 human monocytic cells, a well-established model of human microglia [ 81 ], to demonstrate that treatment with either MH or H4 upregulates production of CXCL10 and TNF by this cell type.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gilthorpe et al [ 44 ] observe upregulated chemotaxis and expression of the activation marker major histocompatibility (MHC) class II by primary murine microglia in the presence of extracellular H1. Munemasa [ 43 ] demonstrates in a murine model of primary acute-closure glaucoma that extracellular H2B induces retinal ganglion degeneration, which is presumably mediated by activation of microglia. To date, the only study to document the pro-inflammatory activity of extracellular histones on human microglia-like cells is by Westman et al [ 39 ], who utilize THP-1 human monocytic cells, a well-established model of human microglia [ 81 ], to demonstrate that treatment with either MH or H4 upregulates production of CXCL10 and TNF by this cell type.…”
Section: Discussionmentioning
confidence: 99%
“…Both protective and toxic actions of extracellular MH towards neuronal cells have been reported [40][41][42]. To date, only three studies have investigated the effects of individual histone isoforms on microglia-like cells by measuring their expression of inflammatory markers and cytokines [39,43,44]. To the best of our knowledge, the effects of extracellular histones on microglial phagocytic activity or any of the immunomodulatory functions of astrocytes have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously, activator protein 1 is activated via mitogen‐activated protein kinases (MAPK) [ 57 ]. Eventually, these pathways lead to a rise in the levels of pro‐inflammatory factors, such as TNF‐α, IL‐6, and IL‐1β levels [ 16 , 27 , 58 ]. Due to the release of pro‐inflammatory cytokines, more innate immune cells are recruited and eventually the adaptive immune system is activated.…”
Section: Histone‐mediated Mechanisms Leading To Tissue Damagementioning
confidence: 99%
“…Numerous studies have revealed elevated levels of NET components in coronavirus disease 2019 (COVID-19) patients [7,[9][10][11][12][13]. Extracellular histones act as damage-associated molecular patterns (DAMPs) that can cause cell activation [14] and cell death [8,15] and can invoke an immune response by Toll-like receptor (TLR)activation [16], nucleotide-binding oligomerization domain 2 (NOD2)/nucleotide-binding oligomerization domain-like receptor protein 3 (NLRP3) activation [17], and complement activation [18]. Neutralization of extracellular histones by complexation [8,[19][20][21] or proteolysis [22] has been shown to be beneficial in the reduction of tissue and organ damages.…”
Section: Introductionmentioning
confidence: 99%